Leaf Gas Exchange and Root Nodulation Respond to Planting Density in Soybean [Glycine max (L) Merrill] - Louis Hortensius Mwamlima; Josephine Pamela Ouma; Erick Kimutai Cheruiyot (Advances in Agriculture)
Planting density influences structural characteristics and affects mineral nutrient acquisition, irradiance and photosynthesis amongst plants. An experiment was conducted to determine the effect of planting density on leaf gas exchange and nodulation of soybean (Glycine max (L) Merrill). The experiment was conducted as a randomized complete block design (RCBD) in a 5 by 2 factorial treatment arrangement and was replicated three times. Planting density (10, 12, 20, 40, and 80 plants m−2) and soybean varieties (EAI 3600 and DPSB 19) were first and second factors, respectively. Collected data were subjected to analysis of variance in GENSTAT. Significantly different treatment means were separated using Tukey’s honestly significant difference test at 0.05 significance level. Higher planting density significantly increased (p<0.001) interception of photosynthetically active radiation. Increasing number of plants per unit area significantly (p<0.001) reduced root nodulation, stomata conductance, sub-stomatal CO2 concentration, photosynthetic and transpiration rates. Total chlorophyll content was not responsive to planting density though concentration of chlorophyll “a” content was significantly (p<0.005) higher at lower plant density than at higher plant density. Soil moisture status increased with reduction in plant density. Indeterminate variety DPSB 19 had higher rates of stomata conductance, photosynthesis and sub-stomatal CO2 concentration compared to determinate variety EAI 3600.